Assessing intermodal transportation planning at state departments of transportation. (5th June 2007) - Goetz, Andrew R.; Szyliowicz, Joseph S.; Vowles, Timothy M.; Taylor, G. Stephen
We assessed the practice of freight and passenger intermodal planning at seven state departments of transportation Alabama, Arizona, Colorado, Florida, Louisiana, Mississippi, and Texas through analyses of previous studies, long- and short-range plans, organisational structures, surveys, and interviews. Results indicate that these states have altered their organisational structures and have produced plans that increasingly reflect an intermodal orientation, but that Florida and Louisiana were rated somewhat higher. Specific intermodal projects, public participation, and coordination among agencies tended to be rated more highly, while funding for and state DOT attitudes toward transit, bicycle/pedestrian, and intermodal connectors were rated much lower.